Evaluating Family Physicians’ Knowledge of Urinary Tract Infection in Southern Iran: Scale Development - Hourvash Haghighinejad; Parisa Jooya; Raziye Saeedizade; Kaveh Taghipour; Fatemeh Malekpour (Urogenital Tract Infection, 2023)
Purpose Urinary tract infections (UTIs) often present with nonspecific symptoms in childhood and can result in serious complications. Therefore, it is imperative for the proper diagnosis, treatment, and follow-up of this affliction. We first designed a valid and reliable questionnaire. Subsequently, the study evaluated the knowledge of family physicians regarding pediatric UTI. Materials and Methods A questionnaire was designed to evaluate the family physicians’ knowledge of pediatric UTIs. The face and content validity and reliability of the questionnaire were first evaluated in a pilot study. Subsequently, doctors were asked to complete the questionnaire and data-collecting form delivered at their workplace. Results The validity and reliability of the questionnaire were deemed acceptable after omitting two questions. Cronbach's alpha of the final questionnaire was 0.71. More than 75% of the participants answered each question correctly. Approximately 50% of the physicians were post-graduates. Age was determined to be negatively correlated, and the “number of years of graduation” was positively correlated with the total score of the questionnaire. Conclusions The designed questionnaire had acceptable validity and reliability. Moreover, family physicians’ knowledge of pediatric UTIs was found to be favorable.